BISNIS DALAM PERSPEKTIF ISLAM (Telaah Aspek Keagamaan dalam Kehidupan Ekonomi) (Mazahib, 2007)
Business in Islamic perspective is not only simply material ends but also immaterial ones. Given this, business in Islam must be carried out professionally and compatible to Syariah values. This is so since business in Islam has two dimensions: vertical and horizontal. The Koran therefore has offered the concept of business without loss (tijaratan lan taburra) to all businessmen, i.e. despite losing financially, yet making a profit in the form of religious rewards. Accordingly, this kind of business can only be acquired by observing carefully the vertical and horizontal dimension of business in Islam.